Hypoxia Inducible Factor-1α Through ROS/NLRP3 Pathway Regulates the Mechanism of Acute Ischemic Stroke Microglia Scorching Mechanism - Ma X; Jiao J; Aierken M; Sun H; Chen L (Biologics: Targets & Therapy, 2023)
Xin Ma,* Junxia Jiao,* Mayila Aierken,* Hong Sun, Li Chen Department of Clinical Laboratory, Urumqi Friendship Hospital, Urumqi, Xinjiang Uygur Autonomous Region, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong Sun; Li Chen, Department of Clinical Laboratory, Urumqi Friendship Hospital, No. 558 Shengli Road, Tianshan District, Urumqi, Xinjiang Uygur Autonomous Region, 830049, People’s Republic of China, Tel +86-13899816208 ; +86-13579401192, Email ma.xin228@163.com; CLDYX624@163.comPurpose: In vitro experiments explored how the hypoxia-induced factor-1α (HIF-1α) regulates the regulation of pyroptosis in microglial cells (BV 2) in acute ischemic stroke through ROS/NLRP3 pathway.Methods: The microglia acute phase oxygen-glucose deprivation/reoxygenation (OGD/R) was established, CCK-8 was applied to determine the optimal timing of intervention modeling. HIF-1α was overexpressed with stabilizer GF-4592 and HIF-1α small molecule interfering RNA (HIF-1α-siRNA), which was divided into group A (blank group), group B (OGD/R model group), group C (model+FG-4592 intervention group), group D (model+siRNA negative control group) and group E (model+HIF-1α-siRNA group). Cell proliferation of different groups was measured by CCK-8 assay. Pyroptosis and intracellular ROS levels were measured by flow cell technology. IL-18, IL-1β levels were measured by ELISA. HIF-1α, GSDMD-D, GSDMD-N, clean-Caspase-1 and NLRP3 protein expression levels were measured by Western blot. On the above experiments, ROS and NLRP3 response experiments were performed to explore how HIF-1α regulates pyroptosis through ROS/NLRP3 pathway.Results: Hypoxia for 6 h then reoxygenation for 12 h was the optimal intervention time. Compared with groups B and D, cell proliferation in group C was significantly enhanced, pyroptosis, intracellular levels of ROS, IL-18, IL-1β and the expression of GSDMD-D, GSDMD-N, clean-Caspase-1, and NLRP3 proteins were significantly decreased in group C (P < 0.05). However, in group E, the performance of these test indicators were exactly the opposite, and the difference was statistically significant (P < 0.05). Through ROS and NLRP3 response experiments, it was found that HIF-1α Inhibition of Pyroptosis by inhibiting ROS/NLRP3 pathway.Conclusion: Overexpression of HIF-1α factor can inhibit microglia pyroptosis. HIF-1α factor has an inhibitory effect on the ROS/NLRP 3 pathway, which can inhibit the pyroptotic process in microglia.Keywords: hypoxia-inducible factor-1α, acute ischemic stroke, microglial pyroptosis, reactive oxygen species, nucleotide-binding oligomerization domain-like receptor protein 3